Transnational civil society's ability to successfully influence state actors on human rights issues through international non-governmental organizations (INGOs) : a case study of the coalition to stop the use of child soldiers - VerHage, Alicia (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2009)
The international dilemma of child soldiers is a humanitarian concern throughout the world. The Coalition to Stop the Use of Child Soldiers (CSUCS) began in 1998 and is currently the leading collaborative movement to address the issue. However, because of its emphasis on a universal 'Straight 18' approach and support of the Optional Protocol of the Convention on the Rights of a Child (CRC), the CSUCS ignores contextual realities that affect the implementation ofthe international legislation and the development of norms concerning child soldiers. This research project will examine the current international nongovernmental organization (INGO) response to child soldiers- focusing on the CSCUS - and formulate suggestions for potential avenues to further INGO involvement with policies and projects. The argument is based on a neoliberal institutionalist platform that argues in favour ofiNGOs' ability to successfully influence actions taken by state actors to address human right issues. Highlighting the successful INGO influence on states during the International Campaign to Ban Landmines, I will present this example as a potential model for the Coalition to Stop the Use of Child Soldiers, and explore the feasibility of this model whilst making suggestions for more effective involvement of INGOs with regard to the issue of child soldiers.
Keywords: International Campaign to Ban Landmines; Convention on the Rights of the Child (1989 November 20); Non-governmental organizations; Child soldiers; Children's rights; Human rights; Children (International law)